Access and Ease of Use of Open Source Library Management Software by Librarians in University Libraries in North-Central Nigeria - Ango, Abubakar Aliyu; Akporhonor, Blessing Amina (Communicate: Journal of Library and Information Science, 2024)
This study investigated librarian’s access and ease of use of open source library management software in university libraries in North-Central Nigeria. Two research questions were investigated, and one hypothesis was tested at a significance level of 0.05. A descriptive survey design employing total enumeration sampling was utilized to examine a sample population comprising 301 librarians. Data collection was conducted through a questionnaire. Analytical methods included frequency, mean, and standard deviation for the research questions, while the Pearson Product Moment Correlation Coefficient was applied to test the hypothesis at the 0.05 significance level. Results indicated a significant association between access and ease of use of OSLMS in university libraries. Additionally, the study found a high level of ease of use and access to OSLMS among librarians. Recommendations included the adoption of various training platforms such as workshops, seminars, and conferences to maintain proficiency in OSLMS usage, alongside ongoing upgrades to hardware and software for enhanced task performance, safety, efficiency, error tolerance, and user-friendliness.